CAN FINANCIAL RATIOS AFFECT PROFIT GROWTH IN FOOD AND BEVERAGE COMPANIES? - Vensca, Serly Novelya; Mas'adah, Ninik; Astuti, Suryani Yuli (UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to ascertain how the dependent variable, profit growth, is affected by the independent variables, namely profitability (measured by return on assets; ROA), liquidity (measured by current ratio; CR), solvency (measured by debt-to-assets ratio; DAR); and company size (measured by total assets; TA). The companies that manufacture food and beverages and are listed on the Indonesia Stock Exchange between 2012 and 2021 were the subject of this research. The 178 manufacturing businesses that were registered on the Indonesia Stock Exchange comprised the study's population. The quantitative method is used in this research, and the sample analysis technique is purposive. We developed the selection criteria and obtained a sample size of eighteen manufacturing companies operating in the food and beverage subsector between 2012 and 2021. According to the study's results, business size and profitability have a big, positive influence on profit growth. The liquidity variable significantly hampers the rise in earnings. In contrast, the solvency variable does not impact the profit growth variable much. With the research results obtained, the hope is that investors can choose which stocks with high-profit growth in the food and beverage sector to invest in.